Functional Renal MRI - V. Prasad, Pottumarthi; Haque, Muhammad (Current Medical Imaging, 2012)
The article provides a broad overview of functional MRI methods for evaluating the kidney. While the major function of the kidney is excretion and maintenance of homeostasis, functional MRI methods include several techniques that provide tissue characterization above and beyond anatomical depiction. We have divided the review under two major sub-sections based endogenous and exogenous contrast mechanisms. Diffusion MRI, Arterial spin labeling based perfusion MRI, blood oxygenation level dependent (BOLD) MRI, and sodium MRI are discussed under endogenous contrast methods. Dynamic contrast enhanced methods to evaluate renal perfusion and excretory function are covered under exogenous contrast mechanisms. A brief discussion on hyperpolarized MRI and pH measurements is also included. While many of the methods are still considered investigational, where available we have included clinical examples.
Keywords: arterial spin labeling (ASL)